Upper surface thickening construction method and permeable primer

JP2025021182APending Publication Date: 2025-02-13SHO BOND CONSTRUCTION CO LTD +7
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
JP2023124949
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2023-07-31
Publication Date
2025-02-13

AI Technical Summary

Benefits of technology

【0019】 請求項1~4に係る発明によれば、通常上面増厚工法に使用されているエポキシ樹脂系のプライマーと比べて粘度を下げることができるため、浸透性が高く引張応力が働くコンクリート床版の下面側まで達したマイクロクラックも補修することができる。このため、上面増厚工法により補修したコンクリート床版が高い疲労耐久性を発揮することができる。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025021182000001_ABST
    Figure 2025021182000001_ABST
Patent Text Reader

Abstract

To provide a permeable primer which has high permeability and can repair a micro crack reaching the lower surface side of a concrete floor slab on which tensile stress acts, and an upper surface thickening construction method.SOLUTION: An upper surface thickening construction method of thickening concrete of the upper surface of concrete slab includes a permeable primer application step of applying a permeable primer composed of a (meth)acrylic radical curable resin, an adhesive application step for, after the permeable primer is cured, applying a placing joint adhesive consisting of an epoxy resin to the coating surface of the cured permeable primer, and a thickening material placing step for placing a cementitious thickening material for thickening on the coating surface of the placing joint adhesive.SELECTED DRAWING: Figure 1
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a method for increasing the thickness of an upper surface of a concrete floor slab and a penetrating primer used in the method. [Background technology]

[0002] The concrete deck of a road bridge may develop cracks due to the long-term load caused by vehicles passing over it. One method for improving the fatigue durability of a concrete deck that has become damaged in this way is the top surface thickening method, in which SFRC (steel fiber reinforced concrete) is poured onto the top surface of the concrete deck.

[0003] Furthermore, as a measure to prevent peeling of the adhesion interface after the top surface thickening, a top surface thickening method has been developed in which a joint adhesive made of a highly durable epoxy resin is applied to the top surface of the concrete deck slab before SFRC (steel fiber reinforced concrete) is poured (see claim 1 in the claims of Patent Document 1, paragraphs

[0022] to

[0034] of the specification, etc.).

[0004] However, these conventional top surface thickening methods were unable to repair the extremely fine cracks that had occurred on the top surface of the concrete deck, and in order to further improve fatigue durability, there was a demand for a top surface thickening method that could penetrate and repair even the finest cracks.

[0005] For this reason, for example, Non-Patent Document 1 considers a top surface thickening method in which a low-viscosity penetrating primer made of epoxy resin is applied, and then a joint adhesive made of epoxy resin is applied again before the primer hardens, and then SFRC (steel fiber reinforced concrete) is poured (see, for example, pp. 129-134 of Non-Patent Document 1).

[0006] The upper surface thickening method described in Non-Patent Document 1 is capable of repairing microcracks (very fine cracks) that occur near the surface of a concrete deck. However, a penetrating primer made of epoxy resin has a limit to how much it can reduce the viscosity, and its permeability is insufficient to repair deep cracks that occur in a concrete deck. In particular, if cracks that reach the underside of a concrete deck where tensile stress acts can be repaired, the repair effect is high, so there has been a demand for the development of an upper surface thickening method that can repair deep cracks that reach near the underside.

[0007] Furthermore, Patent Document 2 discloses a concrete structure reinforcing material used in a method for repairing a concrete structure, the concrete structure reinforcing material being characterized in that it is made of a room-temperature curing epoxy resin composition having a viscosity of less than 100 mPa s at 23°C, and a method for repairing a concrete structure using the same (see claims 1 and 7 in the claims of Patent Document 2, paragraphs

[0013] to

[0022] of the specification, etc.).

[0008] Furthermore, paragraph

[0020] of the specification of Patent Document 2 states that "The viscosity of the low-viscosity epoxy resin of the present invention is in a range of less than 100 mPa s at 23°C, and has self-penetrating properties and a reinforcing effect. Although there is no particular lower limit to the viscosity range, the viscosity at 23°C is preferably 10 to 80 mPa s."

[0009] It is believed that the concrete structure repair method described in Patent Document 2 reduces viscosity and enhances crack penetration by incorporating water or a solvent, but the limit of viscosity for solvent-free epoxy resins that are highly effective at repairing cracks is approximately 300 mPa s at 5°C. For this reason, there is a need for the development of a top surface thickening method and a solvent-free penetrating primer that are compatible with not only epoxy resins but also highly alkaline concrete and can effectively repair deep cracks that reach the underside of a concrete deck. [Prior art documents] [Patent documents]

[0010] [Patent Document 1] JP 2010-95959 A [Patent Document 2] JP 2013-256835 A [Non-patent literature]

[0011] [Non-Patent Document 1] Kiyoshi Ito and 3 others, "Development and Construction Examples of Third-Generation Highway Bridge RC Deck Thickening Method," Civil Engineering and Construction Technology Presentation 2016, Japan Society of Civil Engineers, 2016, 11, pp.129-134 Summary of the Invention [Problem to be solved by the invention]

[0012] The present invention has been devised in consideration of the above-mentioned problems, and its object is to provide a penetrating primer and top surface thickening method that can repair microcracks that have high permeability and reach the underside of a concrete deck where tensile stress is applied. [Means for solving the problem]

[0013] The top surface thickening method described in claim 1 is a top surface thickening method for thickening concrete on the top surface of a concrete deck slab, and is characterized by comprising a penetrating primer application step of applying a penetrating primer made of a (meth)acrylic radical curing resin, an adhesive application step of applying a joint adhesive made of an epoxy resin to the applied surface of the hardened penetrating primer after the penetrating primer has hardened, and a thickening material casting step of casting a cement-based thickening material for thickening onto the applied surface of the joint adhesive.

[0014] The upper surface thickening method described in claim 2 is the upper surface thickening method described in claim 1, characterized in that in the penetrating primer application process, a penetrating primer having a viscosity of 300 mPa·s or less at 5°C of a (meth)acrylic radical curing resin is applied.

[0015] The upper surface thickening method described in claim 3 is the upper surface thickening method described in claim 1, characterized in that in the penetrating primer application process, a penetrating primer having a viscosity of 70 mPa·s or less at 5°C of a (meth)acrylic radical curing resin is applied.

[0016] The upper surface thickening method described in claim 4 is characterized in that, in the penetrating primer described in claim 2 or 3, in the penetrating primer application step, a penetrating primer having a petroleum wax content of 0.03% or more and 0.2% or less contained in a (meth)acrylic radical curing resin is applied.

[0017] The penetrating primer described in claim 5 is a penetrating primer used in a top surface thickening method for thickening concrete on the top surface of a concrete deck, characterized in that it is made of a (meth)acrylic radical curing resin, has a viscosity of 300 mPa s or less at 5°C, and has a petroleum wax content of 0.03% or more and 0.2% or less.

[0018] The penetrating primer described in claim 6 is a penetrating primer used in a top surface thickening method for thickening concrete on the top surface of a concrete deck, and is characterized in that it is made of a (meth)acrylic radical curing resin and contains a methyl methacrylate crosslinking reaction type acrylic resin and an epoxy acrylate resin. Effect of the Invention

[0019] According to the inventions of claims 1 to 4, the viscosity can be reduced compared to the epoxy resin-based primers normally used in the top surface thickening method, so that microcracks that reach the bottom surface of the concrete slab, which has high permeability and where tensile stress acts, can be repaired. Therefore, the concrete slab repaired by the top surface thickening method can exhibit high fatigue durability.

[0020] In particular, according to claims 2 and 3, it is possible to repair microcracks that reach the underside of a concrete slab, which has high permeability and is subject to tensile stress.

[0021] In particular, according to claim 4, a primer made of a normal (meth)acrylic radical curing resin contains petroleum wax to enhance surface curing properties, and the content of the petroleum wax contained is 0.03% or more and 0.2% or less, so that the surface curing properties are good and the adhesion with the joint adhesive made of an epoxy adhesive can be enhanced.

[0022] According to claim 5, the viscosity can be reduced compared to the epoxy resin primers normally used in the top surface thickening method, so that microcracks that have reached the bottom surface of the concrete slab, where tensile stress acts and have high permeability, can be repaired. As a result, the concrete slab repaired by the top surface thickening method can exhibit high fatigue durability.

[0023] According to claim 6, the viscosity can be reduced, so not only can microcracks that reach the underside of the concrete slab, where tensile stress is applied and high permeability, be repaired, but also the adhesion to the joint adhesive made of epoxy resin is improved. Therefore, the concrete slab repaired by the upper surface thickening method can exhibit high fatigue durability. [Brief description of the drawings]

[0024] [Figure 1] FIG. 1 is a vertical cross-sectional view showing a schematic diagram of an existing concrete deck repaired using a top surface thickening method according to an embodiment of the present invention, where (a) shows the state before construction and (b) shows the state after construction. [Diagram 2] FIG. 2 is a vertical cross-sectional view showing a schematic diagram of an existing concrete slab repaired by the top surface thickening method, where (a) shows a conventional embodiment and (b) shows an embodiment of the present invention. [Diagram 3] FIG. 3 is a schematic diagram showing typical stresses acting on a concrete deck. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0025] Hereinafter, a penetrating primer according to an embodiment of the present invention and a method for increasing the thickness of a top surface of a concrete floor slab using the same will be described in detail with reference to the drawings.

[0026] <Top surface thickening method> A method for thickening the upper surface of a concrete slab using a penetrating primer according to an embodiment of the present invention will be described. FIG. 1 is a vertical cross-sectional view showing a typical case where an existing concrete slab is repaired by the method for thickening the upper surface according to an embodiment of the present invention, where (a) shows the state before construction and (b) shows the state after construction. FIG. 2 is a vertical cross-sectional view showing a typical case where an existing concrete slab is repaired by the method for thickening the upper surface, where (a) shows a conventional embodiment and (b) shows an embodiment of the present invention. Note that the dimensions in the figure are examples for a typical concrete slab, and it goes without saying that they may be set appropriately according to the situation at the site.

[0027] The top surface thickening method according to an embodiment of the present invention is a reinforcement method in which a thickening material C1 such as fiber-reinforced concrete is poured onto the top surface of an existing concrete deck CS to integrate it with the existing concrete deck CS, thereby increasing the thickness of the concrete deck and improving its bending strength and punching shear strength.

[0028] (Asphalt pavement removal process) First, in the upper surface thickening method according to this embodiment, an asphalt pavement removal step is performed to remove the asphalt pavement AP shown in FIG. 1(a).

[0029] At this time, as shown in Figure 1(b), the top surface of the existing concrete deck CS is excavated about 10 mm for the purpose of roughening. This is to improve the unity with the thickening material C1 that will be poured later. In this process, concrete dust is removed by grinding (cleaning) with steel shot blasting etc. so as not to impair the adhesion of the penetrating primer PP that will be applied in a later process.

[0030] (Penetrating primer application process) Thereafter, in the upper surface thickening method according to the present embodiment, as shown in Fig. 1(b), a penetrating primer application step is performed in which a penetrating primer PP made of a (meth)acrylic radical curing resin is applied. Here, the (meth)acrylic radical curing resin generally refers to a thermosetting resin whose main components are acrylic acid, methacrylic acid, their esters, and acrylic monomers that are derivatives of these, and which contains reactive functional groups such as hydroxyl groups, acid groups, N-methylol groups, and unsaturated groups. The penetrating primer PP according to the present embodiment contains epoxy acrylate resin and various modified substances as acrylic resins.

[0031] In particular, among acrylic resins, methyl methacrylate crosslinking reaction type acrylic resin and epoxy acrylate resin are preferred. As described in JP-A-10-88820, acrylic resins containing methyl methacrylate crosslinking reaction type acrylic resin and epoxy acrylate resin can exhibit excellent adhesion between the concrete surface and the permeable waterproof layer even when construction is performed in a low temperature environment or a wet environment, and construction can be performed in a short time.

[0032] At this time, in this step, it is preferable to apply a penetrating primer PP in which the viscosity of the (meth)acrylic radical curing resin at 5° C. is 300 mPa·s or less. The limit of the viscosity of epoxy resin is about 300 mPa·s at 5° C. By setting the viscosity at 300 mPa·s or less, as shown in Fig. 2(b), it is possible to repair even minute microcracks by penetrating them, as compared to the top surface thickening method according to the conventional embodiment in which the epoxy resin shown in Fig. 2(a) is used as the joint adhesive JA or its primer, and it is possible to improve the fatigue durability of the reinforced concrete floor slab.

[0033] Furthermore, in this process, it is even more preferable to apply a penetrating primer PP in which the viscosity of the (meth)acrylic radical curing resin at 5°C is 70 mPa s or less. Furthermore, by lowering the viscosity of the penetrating primer PP and increasing its permeability, it is possible to repair deep microcracks that reach the underside of the existing concrete deck CS shown in Figure 2(b), and improve the fatigue durability of the edge of the underside of the existing concrete deck CS where tensile force acts.

[0034] Furthermore, in this step, it is preferable to use a (meth)acrylic radical curing resin containing a methyl methacrylate crosslinking reaction type acrylic resin and an epoxy acrylate resin as the penetrating primer PP in order to enhance adhesion with the joint adhesive JA made of an epoxy resin that is applied on the penetrating primer PP in a subsequent step.

[0035] In addition, (meth)acrylic radical curing resins generally contain petroleum wax to enhance surface curing. This is because petroleum wax forms a coating on the surface of the coating when the primer is applied, and has the function of suppressing curing inhibition caused by oxygen. However, in the upper surface thickening method according to the present embodiment, the (meth)acrylic radical curing resin is used in a special manner in which a joint adhesive JA made of an epoxy resin is applied on top of the penetrating primer PP. The inventors of the present application have found that the petroleum wax contained in the (meth)acrylic radical curing resin inhibits adhesion to the joint adhesive JA made of an epoxy resin.

[0036] Therefore, in this step, it is preferable to use a (meth)acrylic radical curing resin as the penetrating primer PP and to set the content of petroleum wax contained in the (meth)acrylic radical curing resin to 0.03% (mass %, the same applies below) or more and 0.2% or less. If the petroleum wax is less than this lower limit, the surface curing property may deteriorate, and if it exceeds the upper limit, it inhibits adhesion with the joint adhesive JA made of epoxy resin.

[0037] In addition, when using a (meth)acrylic radical curing resin as a penetrating primer PP, it is considered advantageous to include methyl methacrylate, which has low viscosity and excellent curing properties. However, since methyl methacrylate is highly volatile and has a specific odor, it is required to reduce its content in order to reduce flammability and improve the working environment. Therefore, by including petroleum wax in the (meth)acrylic radical curing resin, it is possible to reduce the content of methyl methacrylate while maintaining surface curing properties.

[0038] Petroleum wax refers to wax derived from petroleum, and is broadly classified into three types according to the Japanese Industrial Standards: paraffin wax, microcrystalline wax, and velouratum. Of these, paraffin wax is the most preferred petroleum wax.

[0039] (Adhesive application process) Next, in the top surface thickening method according to this embodiment, after the penetrating primer PP applied in the previous process has hardened, an adhesive application process is performed in which a joint adhesive JA made of an epoxy resin is applied to the applied surface (upper) of the hardened penetrating primer. This is to improve the unity between the existing concrete slab CS and the thickening material C1.

[0040] However, since (meth)acrylic radical curing resins will not cure properly if a joint adhesive JA made of an epoxy resin is applied before the resin cures, in the top surface thickening method according to the present embodiment, it is necessary to apply the joint adhesive JA after confirming that the penetrating primer PP has cured. In addition, from the viewpoint of shortening the construction time, it is preferable that the penetrating primer PP has a curing time of 1 hour or less.

[0041] Here, epoxy resin is a general term for a thermosetting resin that is a compound having one or more epoxy groups in the molecule and can be cured by constructing a crosslinked network with the epoxy groups. Examples of epoxy resins include bisphenol A type epoxy resin obtained by condensation reaction of bisphenol A and epichlorohydrin, bisphenol F type epoxy resin, bisphenol AD ​​type epoxy resin, phenol novolac type epoxy resin, cresol novolac type epoxy resin, glycidyl ester type epoxy resin, biphenyl type epoxy resin, and polymer type epoxy resin.

[0042] In particular, the adhesive JA made of epoxy resin is preferably one that uses a base agent of bisphenol A type epoxy or bisphenol F type epoxy and a polyamine-based or mercaptan-based hardener. The adhesive JA may contain a coupling agent, a viscosity modifier, a hardening accelerator, etc. in addition to the base agent and hardener.

[0043] (Thickening material pouring process) Next, in the top surface thickening method according to this embodiment, a thickening material pouring process is carried out in which a thickening material C1 for thickening is poured onto the applied surface of the joint adhesive JA applied in the previous adhesive application process.

[0044] In the top surface thickening method according to this embodiment, fiber reinforced concrete (FRC) is poured as the thickening material C1, which is made by mixing metal fibers such as steel fibers, inorganic fibers such as glass fibers or carbon fibers, or relatively strong synthetic fibers such as aramid fibers, polyolefin fibers, and vinylon fibers into concrete, so that the thickening material can withstand repeated loads.

[0045] However, the thickening material C1 is not limited to fiber-reinforced concrete, and may be cast-in-place reinforced concrete in which ordinary concrete containing fine aggregate, coarse aggregate, and cement is reinforced with rebar. The thickening material C1 may also be ordinary mortar containing fine aggregate and cement. In short, the thickening material C1 may be any cement-based thickening material containing a cement component.

[0046] Here, various cements such as normal Portland cement, high-early-strength Portland cement, ultra-high-early-strength Portland cement, moderate-heat Portland cement, or low-heat Portland cement can be used as the cement to be mixed into the cement-based thickening material. Depending on the purpose, the cement to be used may be a mixed cement such as blast-furnace cement, fly ash cement, or silica cement, or a special cement such as an expansive cement or a low-heat cement. Depending on the purpose, various admixtures such as a water-reducing agent, a high-performance water-reducing agent, an air-enhancing agent, a setting retarder, or an expansion agent may be added to the cement-based thickening material.

[0047] When the thickening material C1 poured in this process hardens and attains the specified strength, the top surface thickening method according to this embodiment is completed.

[0048] Thus, according to the upper surface thickening method of this embodiment, a penetrating primer application step is performed in which a (meth)acrylic radical curing resin is applied as the penetrating primer PP, and an adhesive application step is performed in which a joint adhesive JA made of an epoxy resin is applied to the applied surface (upper) of the cured penetrating primer. The (meth)acrylic radical curing resin can have a lower viscosity than the epoxy resin-based primer normally used in the upper surface thickening method.

[0049] Therefore, according to the top surface thickening method of this embodiment, as shown in Fig. 2, the (meth)acrylic radical curing resin with reduced viscosity and increased permeability can repair microcracks that reach the underside of the existing concrete slab CS where tensile stress acts, and the epoxy resin joint adhesive JA can ensure the integrity of the existing concrete slab CS and the thickening material C1. Therefore, the concrete slab (CS+C1) repaired and thickened by the top surface thickening method can exhibit high fatigue durability.

[0050] Here, as shown in Figure 3, a compressive force acts on the upper edge of the concrete slab, and a tensile force always acts on the lower edge. Therefore, microcracks that reach the underside of the existing concrete slab CS are always subjected to a tensile force in the direction of being pushed open, which is likely to develop into larger cracks in the future and have a negative impact on fatigue durability. Therefore, when repairing with the top surface thickening method, it is extremely important in terms of improving fatigue durability to be able to repair microcracks that reach the underside of the existing concrete slab CS by penetrating a penetrating primer. Figure 3 is a schematic diagram showing the general stresses acting on a concrete slab.

[0051] In addition, according to the top surface thickening method of this embodiment, the content of petroleum wax contained in the (meth)acrylic radical curing resin is set to 0.03% or more and 0.2% or less, so that the adhesion of the (meth)acrylic radical curing resin to the joint adhesive JA made of an epoxy resin can be ensured while maintaining the surface curability of the (meth)acrylic radical curing resin.

[0052] Although the penetrating primer and the method for thickening the upper surface using the same according to the embodiment of the present invention have been described in detail above, the above-mentioned and illustrated embodiments are merely specific embodiments for carrying out the present invention, and therefore the technical scope of the present invention should not be interpreted as being limited by them.

[0053] <Penetrating primer> [Effectiveness verification test] Next, in order to confirm the effects of the penetrating primer of the present invention and the top surface thickening method using it, a total of 12 types of penetrating primers were created, consisting of 11 examples and one comparative example (conventional embodiment), and tests were conducted to confirm the penetration depth and adhesion with joint adhesive.

[0054] In Examples 1 to 5, five types of penetrating primers containing 50% methyl methacrylate and different petroleum wax contents with a viscosity of 18 mPa s at 5°C were obtained by mixing "Primer P100" manufactured by DIC Corporation as a penetrating primer made of a (meth)acrylic radical curing resin and paraffin wax (melting point 48°C) as a petroleum wax in a predetermined ratio.

[0055] In addition, for Examples 6 to 11, six types of penetrating primers containing 30% methyl methacrylate and different petroleum wax contents and having a viscosity of 70 mPa s or less at 5°C were obtained by mixing "Primer P-100" manufactured by DIC Corporation, which contains 50% methyl methacrylate as a (meth)acrylic radical curable resin, "Neomer BA-641" manufactured by Sanyo Chemical Industries, Ltd., which contains no methyl methacrylate, and paraffin wax (melting point 48°C) as a petroleum wax in a predetermined ratio.

[0056] In addition, in Comparative Example 1, "Smart Bond Primer" made by NIPPO Corporation and made of epoxy resin was used as a primer with a viscosity of 770 mPa·s at 5°C.

[0057] (Crack repair effect: performance test of penetrating waterproofing material) To confirm the crack repair effect, the test was conducted in accordance with the performance test of the penetrating waterproofing material described in the Metropolitan Expressway Company Limited's "Pavement Planning and Construction Guidelines" (October 2021), and the penetration depth at 5°C was evaluated. In addition, in the test, the application amount of the penetrating primer was 0.35 kg / m 2 The average penetration depth was rated as ◯ when it was 50 mm or more, and × when it was less than 50 mm.

[0058] (Adhesion to joint adhesive: Adhesive strength) In order to confirm the adhesion with the joint adhesive, a test specimen was prepared in accordance with NEXCO Test Method 434, and an adhesion test was conducted to evaluate the adhesion strength. The joint adhesive used was "Smart Bond JT" made by NIPPO Corporation, which is made of epoxy resin. The results of each test are shown in the following table.

[0059] [Table 1]

[0060] As is clear from Table 1, the primers of Examples 1 to 5 all have high crack repair effect and high fatigue durability. However, when the petroleum wax content is up to 0.2%, the fatigue strength is 1.0 N / mm 2 However, when the petroleum wax content exceeded 0.2%, the petroleum wax had a large effect of inhibiting adhesion to the joint adhesive, resulting in a bond strength of 1.0 N / mm 2 For this reason, it can be said that the content of the petroleum wax contained in the (meth)acrylic radical curing resin as a penetrating primer is preferably 0.2% or less.

[0061] It was also found that the primers of Examples 6 to 11 all had a high crack repair effect and high fatigue durability. However, when the petroleum wax content was less than 0.03%, the surface hardening of the primer was poor due to the small petroleum wax content, and the hardness of the primer was 1.0 N / mm 2 No adhesion strength as high as this was obtained. For this reason, it can be said that the content of petroleum wax contained in the (meth)acrylic radical curing resin as a penetrating primer is preferably 0.03% or more. In addition, the primers of Examples 6 to 11 have a reduced content of methyl methacrylate compared to the primers of Examples 1 to 5, and therefore have a reduced surface curability.

[0062] In contrast, Comparative Example 1 had an adhesive strength of 2.3 N / mm 2 However, the viscosity was high and the penetration into the cracks was insufficient, so a high crack repair effect could not be confirmed. Therefore, it can be said that the repair effect of using epoxy resin as a penetrating primer is insufficient (see also Figure 2(a)). [Explanation of symbols]

[0063] CS: (Existing) concrete floor slab AP: Asphalt pavement C1: Additive concrete PP: Penetrating primer JA: Joint adhesive

Claims

1. A top surface thickening method for thickening concrete on the top surface of a concrete floor slab, The method includes a penetrating primer application step of applying a penetrating primer made of a (meth)acrylic radical curing resin, an adhesive application step of applying a joint adhesive made of an epoxy resin to the applied surface of the hardened penetrating primer after the penetrating primer has hardened, and a thickening material casting step of casting a cement-based thickening material for thickening the applied surface of the joint adhesive. A top surface thickening method characterized by:

2. In the penetrating primer application step, a penetrating primer having a viscosity of 300 mPa·s or less at 5° C. is applied. The method for increasing thickness on an upper surface according to claim 1 .

3. In the penetrating primer application step, a penetrating primer having a viscosity of 70 mPa·s or less at 5° C. is applied. The method for increasing thickness on an upper surface according to claim 1 .

4. In the penetrating primer application step, a penetrating primer having a petroleum wax content of 0.03% or more and 0.2% or less contained in a (meth)acrylic radical curable resin is applied. The method for increasing the thickness of an upper surface according to claim 2 or 3, characterized in that

5. A penetrating primer used in a top surface thickening method for thickening concrete on the top surface of a concrete floor slab, The composition is made of a (meth)acrylic radical curing resin, has a viscosity of 300 mPa·s or less at 5°C, and contains petroleum wax in an amount of 0.03% or more and 0.2% or less. A penetrating primer characterized by:

6. A penetrating primer used in a top surface thickening method for thickening concrete on the top surface of a concrete floor slab, The composition is made of a (meth)acrylic radical curing resin, and contains a methyl methacrylate crosslinking reaction type acrylic resin and an epoxy acrylate resin. A penetrating primer characterized by:

Citation Information

Patent Citations

  • Adhesion overlay method for existing concrete pavement

    JP2010095959A

  • Concrete structure repairing method

    JP2013256835A